Awareness of hibah: a case study among Muslim residents in Seremban, Negeri Sembilan / Muhammad Alif Syazwan Abu Bakar - Abu Bakar, Muhammad Alif Syazwan (2022)
Nowadays, the existence of unclaimed property upon the owner’s death is keep increasing. Hibah is one of estate management planning in Islam, which is not widely practiced by Muslims in this country. Most of Malaysian Muslims do not understand the concept of hibah because of inadequate knowledge plus they do not really expose with the implementation of hibah. Moreover, they are facing difficulties to whom they should refer to manage their property due to the lack of exposure of hibah practice. This research paper aims to examine the level of Hibah awareness among residences in Seremban, Negeri Sembilan. Hence, this study carries out three objectives: (1) to ascertain the awareness of hibah as an alternative mechanism in Islamic wealth management among Muslim residents in Seremban, Negeri Sembilan, (2) to identify factors influenced the awareness of hibah as an alternative mechanism in Islamic wealth management among Muslims in Seremban, Negeri Sembilan, and (3) to propose possible solutions in raising awareness of hibah in wealth management among Muslims especially in Seremban, Negeri Sembilan. This study used quantitative method with a self-administered questionnaire, and the Cronbach’s Alpha coefficient was used to test the reliability of the questions. A questionnaire survey was created, and data were collected from 110 respondents of Seremban residents in Negeri Sembilan state. Based on the data indicated that attitude have the highest significant effect on hibah awareness than knowledge of hibah and social influence.